Study of the prevalence of micro organisms and impact of usage of restricted antibiotics in a tertiary care hospital - DR(BRIG) ANIL PANDIT; DR.AMRUTA PANDIT; DR. SAYAN SAHA (International Journal of Pharma and Bio Sciences, 2017)
The study is to optimize the use of restricted antibiotics, to minimize the consequences of usage of Restricted Antibiotics (RA) & to determine the prevalence of resistant organisms. 316 patients receiving antibiotics in a tertiary care hospital in Kolkata, both restricted as well as non-restricted, were studied. The data was collected, analyzed for microbial & pharmacological impact analysis 316 patients under study, a total of 3218 antibiotics were dispensed, out of which834were restricted antibiotics (n=3218; 25.92%).The results showed that restricted antibiotic use consisted of 25.92%. According to the for Healthcare Epidemiology of the recommended use stands at 20%. In our study there is an increase of 5.92%. Recommended that health care institutions need robust infection control and antibiotic stewardship programs to prevent transmission of resistant bacteria and to decrease the selective pressure for resistance.